Deskripsi Gejala Stres Akademik dan Kecenderungan Pilihan Strategi Koping Siswa Berbakat - Amy Noerul Azmy; Achmad Juntika Nurihsan; Eka Sakti Yudha (Universitas Mathla'ul Anwar Banten, 2017)
The description of academic stress and tendencies of using coping strategies in the gifted students. This study aims to describe the general conception of an academic stress of gifted students, tendencies of coping strategies they use, and to plan an appropriate guidance and counseling program to manage an academic stress of gifted students. This study used a descriptive method with nonprobability sampling technique and specifically took the sample by using purposive sampling. The sample is collected from gifted students of tenth-graders at SMA Negeri 4 Bandung year 2015/2016. The result showed that academic stress of gifted students is in the medium category with a percentage of 76.92. On the other hand, the tendencies of the gifted students on using coping strategies showed that the students tend to use Emotion Focused Coping, with a percentage of 53.84%. This shows that gifted students need a special attention on how to cope with problems so that it does not result in a negative way. Therefore, an appropriate service that is suitable for the needs of gifted students is required. The recommendation from this study is addressed to the school’s guidance and counseling committee, teachers, and other researchers.